Africando. Statement 1988-2009 and Projects 2010-2018. Vol. I. Report for Research Director Accreditation. - (:unkn) unknown (My University, 2010)
This Research Director Accreditation report was devised as a ‘super activity report' by a researcher two-thirds of the way through his career. It looks back on the main research themes addressed on the Africa of Portuguese colonisation in the 20th century, showing how this is not only ‘deeply rooted' (necessary and demanded) research but also a general contribution to the development of history as a discipline, most notably to the concepts of Creolity, the ‘colonial State' and the ‘nationless State', ‘social body', ethnicity and ‘ nationism', etc. The project part not only sets out the action required to complete the many (delayed) plans, but also proposes an international research programme on coloniality, a concept perceived as being far better than the postcolonial approaches to express the spatial and social heterogeneity of the world, historically built around non-capitalist forms of capitalist domination on the periphery. It shows how the Africa of former Portuguese colonisation is very useful from a heuristic point of view in the study of coloniality.
Keywords: African Research